(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the system of defining values in student youth. Socio–psychological features of the formation of human social behavior determine the degree of its connection with personality behavior, personal and group compatibility of cultural values, influence on public life, analysis of norms and identification of motives for socio-psychological behavior. This system helps to identify various cultural differences and similarities and to understand the basic values that influence behavior.